2007
DOI: 10.1094/pdis-91-5-0616
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Binucleate Rhizoctonia Species Causing Web Blight on Azalea in Mississippi and Alabama

Abstract: Web blight on containerized azalea is an annual problem for commercial nurseries during summer months in the southern United States. Losses to web blight are associated with the cost of fungicide applications, delayed marketing of diseased plants, and plant death. Two hundred and eleven isolates of binucleate Rhizoctonia were recovered from azalea leaves with web blight symptoms from two nurseries in Mississippi and Alabama over 3 years. The internal transcribed spacer region (ITS) of the ribosomal DNA (rDNA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…The ITS data presented here for the extype strain of C. ramicola clearly distinguish it from the morphologically similar C. theobromae. Rinehart et al (2007) and M.A.C., (unpubl.) considered C. ramicola to be most closely related to AG-U of Ceratobasidium (Rinehart et al 2007), a group that is characterized by having binucleate hyphal cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ITS data presented here for the extype strain of C. ramicola clearly distinguish it from the morphologically similar C. theobromae. Rinehart et al (2007) and M.A.C., (unpubl.) considered C. ramicola to be most closely related to AG-U of Ceratobasidium (Rinehart et al 2007), a group that is characterized by having binucleate hyphal cells.…”
Section: Discussionmentioning
confidence: 97%
“…Pure cultures of this Ceratobasidium were isolated from the vascular tissue of wood of diseased cacao in South Sulawesi and East Java. Ceratobasidium ramicola represents a species complex that includes pathogens of azalea and rose in Japan and the USA, respectively (Hyakumachi et al 2005;Rinehart et al 2007) and more recently on carrot in Japan (Tomo Misawa, Shiro Kuninaga & Takashi Toda, unpubl. ).…”
Section: Discussionmentioning
confidence: 99%
“…The close relationship existing within these isolates has been previously recognized (Hyakumachi et al 2005; Rinehart et al 2007; Sharon et al 2008; Veldre et al 2013). Isolates of AG-U have been found to recognize and undergo hyphal fusion (anastomose) with certain isolates of AG-P, and Sharon et al (2008) have suggested that AG-U is a subgroup of AG-P.…”
Section: Discussionmentioning
confidence: 76%
“…the southern and eastern United States (2,13,22). Web blight symp toms typically appear in July and August, but can occur as early as June and as late as September (2,7,8,14).…”
mentioning
confidence: 99%